ANALISIS MINAT BELAJAR SISWA PADA MATA PELAJARAN FISIKA DI SMA N 1 GODEAN DALAM UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA - Razaq, Faishal Fadhila Abdul; Diyana, Tsania Nur (Universitas Tanjungpura, 2023)
This study aims as a preliminary study to determine which factor is the most significant in influencing students' interest in learning physics. The aspects used to determine students' interest in learning are interest or pleasure, attention, awareness, and concentration. The subject of this research was class XI students of SMA Negeri 1 Godean, Special Region of Yogyakarta. Data collection was carried out using a questionnaire using a Likert scale where the questions were adjusted to the aspects of this study studied. The result shows that 28 students fell into the medium category, 3 students entered into the low category, and 5 students entered into the high category. In addition, the average aspect value in influencing student learning interest in the relatedness aspect was 68.75%, the attention aspect was 57.5%, the awareness aspect was 70.9%, and the concentration aspect was 67.5%. Based on the results of the study, it can be concluded that the learning interest of students at SMAN 1 Godean is included in the medium category where the most significant aspect affecting student learning interest is the awareness aspect of 70.9% and the least significant aspect affecting student learning interest is the attention of 57.6%. The implications of this preliminary study will be developed into data and considerations in the development of instructional media in physics subjects.